Geração e proteção de estados comprimidos do campo e estados atômicos emaranhados em cavidades ópticas - Rossatto, Daniel Zini (Universidade Federal de São Carlos, 2010)
In this work we investigated the engineering of interactions and reservoirs in the context of Cavity Quantum Electrodynamics. The investigated system consists of two identical three-level atoms trapped in two distinct traps, but inside the same optical cavity, inte- racting with the cavity mode and driven by classical .elds to manipulate the atom-.eld interaction. First, we assume the atomic system interacts with a high-Q cavity and show how to generate a displaced squeezed state for cavity mode asymptotically, i.e., we con- structed an arti.cial squeezed reservoir for the cavity mode. For this purpose we assume, in addition to the engineered atom-.eld interaction, a strong decay of the atoms (i.e., the atomic decay rate must be much stronger than the e¤ective atom-.eld coupling). Next, considering a cavity with strong decay rate, we investigated how to protect atomic entangled states as the Bell states. Here, the cavity mode acts as an arti.cial squeezed reservoir for the atoms, leading the system to the desired state asymptotically. In both cases, we considered only two e¤ective levels for atoms, reaching an interaction which comprehends the simultaneous implementation of the Jaynes-Cummings and anti- Jaynes-Cummings Hamiltonians.
Keywords: Teoria quântica; Ótica quântica; Eletrodinâmica quântica de cavidades; Engenharia de reservatório; CIENCIAS EXATAS E DA TERRA::FISICA